MALE TERM NEONATE WITH BLADDER EXSTROPHY–EPISPADIAS COMPLEX - Utami Budha, Made Indah Nastiti; Retayasa, I Wayan; Kardana, I Made; *, Bowolaksono; Kawiyana, Ketut Siki (Medicina; Vol 40 No 1 (2009): Januari 2009, 2014)
Bladder exstrophy is a malformation of the bladder, in which the bladder and related structures are turned inside out. Bladder exstrophy affects one in approximately 50,000 livebirths. Male to female ratio is 2.3 : 1. Epispadias is commonly seen with exstrophy of the bladder. The cause and nature of the faulty development is not yet clear. The diagnosis is generally immediately apparent. Bladder exstrophy is a surgical correctable birth defect. In this case, bladder exstrophy–epispadias complex founded in male term neonate. On inspection was founded bladder everted through a midline lower abdominal wall defect, widening of the pubic symphisis and epispadias. Urology ultrasound revealed absent of the right kidney at right fossa renalis or in pelvic cavity, slight hydronephrosis of left kidney, no appearance of bladder in pelvic cavity. Patient underwent surgery during hospitalized in Sanglah Hospital - Denpasar. This patient was referred to the Congenital Anomaly Team in Dr. Soetomo Hospital - Surabaya because there was wound dehiscence during post operation care.[ MEDICINA 2009;40:60-4 ].
Keywords: bladder exstrophy, epispadias, surgical correctable, dehiscence